Autonomías indígenas en la Amazonía peruana. La experiencia del pueblo wampis - Pérez, Wrays; Delgado, Deborah (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
This article presents an account of the memory an historic experience of the Wampis people through different political regimes that have tried to influence and intervene in the governance of the ancestral territory. It wants to offer a vision of their interaction with these regimes, taking as a startpoint their collective memory. The article collects some of the central characteristics of the Wampis’ experience in handling and defending their territory facing the institutional changes that are lived in the high Amazon. So, the article takes into account the problems related to the intensification of the influence of the national Peruvian state and the trade pressure that tries to make deep changes in the territory, due to the extension of legal and illegal border economies, as well as demographic changes. Then, the article shows the response of Wampis, which conforms their proposal of an autonomous territorial government.

Este artículo presenta un recuento de la memoria y la experiencia histórica del pueblo wampis con diferentes regímenes políticos que han buscado influenciar e intervenir en la gobernanza de su territorio ancestral. Busca ofrecer una visión de su interacción con estos regímenes, partiendo de la memoria colectiva de este pueblo. Luego, el artículo recoge algunas de las características centrales de sus experiencias de manejo y defensa territorial frente a los cambios institucionales que se viven en la alta Amazonía. Así, el artículo aborda las problemáticas ligadas a la profundización de la influencia del Estado nacional peruano y de la presión comercial que busca ejercer cambios profundos en el territorio debido a la extensión de economías de frontera legales e ilícitas, así como cambios demográficos. El artículo hace entonces un recuento de las alternativas que el pueblo wampis genera frente a esto y que conforman su propuesta de gobierno territorial autónomo.
Indigenous autonomies in Peruvian Amazon: the experience of the Wampis people
Keywords: Memoria; Gobernanza; Autonomía; Conocimiento ancestral; https://purl.org/pe-repo/ocde/ford#5.04.00